Wadi Ath-Thamad, Jordanien: Nabatäische Wohn- und Wirtschaftsstrukturen im Hochland von Moab - Ladurner, Mechthild (e-Forschungsberichte des DAI, 2023)
The comprehensive analysis of Nabataean remains in the Wadi ath-Thamad, a major river system forming the northern perimeter of the Dhiban Plateau, serves as an exemplary study on settlement patterns, architecture and resource management, characterizing the Moabite region in the Hellenistic – Early Roman Period. The project focuses on the documentation and examination of single farmsteads and agricultural villages in the context of paleoenvironment and anthropogenic landscape. Future research is planned for a documentation of the isochronic organisation of the Petra hinterland; the objective is a comparative study of both environmentally and climatologically differing regions of the Nabatean realm.